Exploring the Impact of Cationic Surfactant Ctab on Bleu Brilliant G 250 De Cosmassie: Implications for Health Management and Environmental Sustainability - Naz, Asma; Akhtar, Muhammad Hasnat; Hassan, Waheed Ul; Ashraf, Fatima; Bukhari, Syed Waqas; Qaiser, Muhammad; Abid, Hafiz Muhammad Usman; Akhter, Farah; Qureshi, Muhammad Saleem; Aziz, Abdul (Journal of Health and Rehabilitation Research, 2024)
Background: Surfactants are ubiquitous in both natural and industrial processes due to their unique ability to reduce surface tension and facilitate interactions between hydrophilic and hydrophobic substances. Cationic surfactants like cetyltrimethylammonium bromide (CTAB) are of particular interest because of their widespread applications in areas such as healthcare and environmental management. The interaction between surfactants and dyes, such as Bleu Brilliant G 250 de Cosmassie, is critical in industrial processes, especially in the textile industry where wastewater treatment poses significant environmental challenges. Objective: The aim of this study was to explore the thermodynamic behavior of CTAB when combined with Bleu Brilliant G 250 de Cosmassie in aqueous solutions at room temperature. It sought to determine the critical micelle concentration (CMC) and the degree of counter-ion dissociation (α), and to calculate the changes in Gibbs free energy (ΔGm), enthalpy (ΔHm), and entropy (ΔSm) of the system. Methods: The study employed conductometric and spectrophotometric techniques to analyze the CTAB-dye interactions. Solutions were prepared with varying concentrations of CTAB and Bleu Brilliant G 250 de Cosmassie in deionized water, ensuring solvent purity through stringent conductivity and pH monitoring. Electrical conductance was measured at different temperatures to determine the CMC, while absorbance spectra were recorded to observe changes in the interaction between the surfactant and dye. The degree of counter-ion dissociation was calculated by the slope ratio method, and thermodynamic parameters were computed using established equations. Results: The conductometric studies revealed an increase in CMC with temperature, indicating a stabilization of surfactant monomers at higher temperatures. For CTAB and Bleu Brilliant system 1, the CMC was found to be 0.8 with α valued at 0.83. For system 2, the CMC values were 1.55 and 1.6 with α values of 1.01 and 0.91, respectively. Thermodynamically, the system displayed a Gibbs free energy of micellization of -33.09 KJ/mol, an enthalpy change of -6.53, and an entropy change of 0.1325 JK^-1 mol^-1. Conclusion: The study concluded that the interaction between CTAB and Bleu Brilliant G 250 de Cosmassie is influenced significantly by temperature, which affects the micellization behavior and thermodynamic properties. The findings contribute to a better understanding of the fundamental thermodynamic parameters influencing surfactant-dye interactions, providing insights that may improve industrial processes and environmental sustainability.